Build Islamic Human Resource Development (I-HRD) in University Based on Islamic Worldview: Build Islamic Human Resource Development (I-HRD) in University Based on Islamic Worldview - Rakhmad Agung Hidayatullah; Fuad Mas’ud; Amir Reza Kusuma; Usmanul Hakim (International Journal of Asian Business and Management, 2023)
HRD strategy is not confined to economic aims only, for it also seeks to ptomote the principle of wider public participation by creating employment through labor-intensive technology, investion in education and training, expanding government programs for social services, creating indegenous managerial, scientific and technical skills and by establishing effective social service institutions. But there are religions and civilizations that have a broader spectrum of views than just a vision of the world, so the meaning of the outlook on life is expanded. Since in English vocabulary there is no proper term for expressing a broader vision of the reality of worldliness other than the words worldview, Muslim scholars take the words worldview (for English expression) for the meaning of a view of life whose spectrum reaches the reality of worldliness and ignorance by adding to the adjectives of Islam. The Conclusion is worldview islam is good idea to build IHRD in University